Women and Spanish fascism : the women's section of the Falange, 1934-1959 - Richmond, Kathleen, 1950- (Routledge/Cañada Blanch studies on contemporary Spain, 2003)
Using forty-five interviews with former members and sympathisers, this book traces the development of the Women's section of the Franco government from its roots in the Spanish fascist party to its role in the dictatorship up to 1959. The study reveals that despite its anti-feminist agenda, the section was, in some areas, a catalyst for women's emancipation in post-Franco Spain.